Temporal and Spatial Distribution of SARS-CoV-2 Aerosols in a Large-Scale Fangcang Shelter Hospital in Shanghai, China - Jiafu Jiang; Zhe Yin; Jing Li; Leili Jia; Rulin He; Wenhui Yang; Jihu Yang; Hang Fan; Sen Zhang; Yunfei Wang; Zengming Zhao; Haoran Peng; et al. (Engineering, 2023)
The coronavirus disease 2019 (COVID-19) pandemic caused by frequently mutating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a worldwide impact. However, detailed data on the potential aerosol transmission of SARS-CoV-2 in real-world and controlled laboratory settings remain sparse. During the COVID-19 pandemic in Shanghai, China in 2022, samples were collected in a Fangcang shelter hospital, a large-scale temporary hospital rapidly built by converting the existing National Exhibition and Convention Center (Shanghai) into a health care facility. Aerosol samples at different sites and intervals around patients and in public areas, surface samples, and pharyngeal swab samples from corresponding patients were included. Samples were tested for SARS-CoV-2 using real-time quantitative polymerase chain reaction (RT-qPCR) assays, followed by sequencing if the cycle threshold (Ct) value was < 30. The positivity rate for SARS-CoV-2 in aerosol samples was high in contaminated zones (37.5%, 104/277), especially around the bed (41.2%, 68/165) and near ventilation inlets (45.2%, 14/31). The prevalence of SARS-CoV-2 around the bed, public areas, and air inlets of exhaust vents fluctuated and was closely related to the positivity rate among patients at corresponding sampling sites. Some surface samples of different personal protective equipment from medical staff had high positivity rates. Sixty sequences of joined ORF1ab and spike genes obtained from sixty samples represented two main clusters of Omicron SARS-CoV-2. There was consistency in virus sequences from the same patient and their environment, and the detected virus sequences matched those of virus strains in circulation during the collection periods, which indicated a high likelihood of cross-contamination in the Fangcang shelter hospital. In summary, the results provide a quantitative and real landscape of the aerosol transmission of SARS-CoV-2 and a patient-centered view of contamination in large and enclosed spaces and offer a useful guide for taking targeted measures to avoid nosocomial infections during the management of SARS-CoV-2 or other respiratory virus diseases in a Fangcang shelter hospital.